SISTEM IRIGASI SUBAK DENGAN LANDASAN TRI HITA KARANA (THK) SEBAGAI TEKNOLOGI SEPADAN DALAM PERTANIAN BERIRIGASI - Windia, Wayan; Pusposutardjo, Suprodjo; Sutawan, Nyoman; Sudira, Putu; Supadmo Arif, Sigit (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005)
Subak system is a custom law community with socio-technical-religious characteristics, consists of a group of farmers that manage irrigation water at their irrigarted area (sawah). The existance of subak irrigation systems are dynamic, due to the socio-cultural conditions of the society. Subak as a irrigation system which is based on Tri Hita Karana (THK) concept, is implemented on the system of irrigation in Bali. Its based on socio-technical concept which technologically integrated with the socio-cultural of the society. Furthermore, the form of subak system as an appropriate technology, is implemented on the form of thinking-pattern, social system, and the development of artefax of the system. The final goals of the system are in order to achieve the harmony and togetherness in the irrigation management.
Keywords: Subak, Ttri Hita Karana, Appropriate Technology.